Associations of Social Vulnerability Index With Pathologic Myocardial Findings at Autopsy - Sunderraj, Ashwin; Rivera, Adovich; Gaddam, Meghna; Kim, Sarah; McCook, Juan; O'Neal, Janelle; Lomasney, Jon; Lloyd-Jones, Donald M.; Baumer, Yvonne; Powell-Wiley, Tiffany M.; Feinstein, Matthew J. (Frontiers in Cardiovascular Medicine, 2021)
Background: Social vulnerability is an important determinant of cardiovascular health. Prior investigations have shown strong associations of social determinants of health with cardiovascular risk factors, imaging findings, and clinical events. However, limited data exist regarding the potential role of social vulnerability and related physiologic stressors on tissue-level pathology. Methods: We analyzed clinical data and linked autopsy reports from 853 decedent individuals who underwent autopsy from 4/6/2002 to 4/1/2021 at a large urban medical center. The mean age at death was 62.9 (SD = 15.6) and 49% of decedent individuals were men. The primary exposure was census-tract level composite social vulnerability index based on the Centers for Disease Control and Prevention Social Vulnerability Index (SVI). Individuals were geocoded to census tracts and assigned SVI accordingly. Four myocardial tissue-level outcomes from autopsy were recorded as present or absent: any coronary atherosclerosis, severe/obstructive coronary atherosclerosis, myocardial fibrosis, and/or myopericardial inflammation. Multivariable-adjusted logistic regression models were constructed with SVI as the primary exposure and covariates including age, sex, race, body mass index (BMI), diabetes, and hypertension. Additional analyses were performed stratified by clinical diagnoses of heart failure (HF) and coronary artery disease (CAD). Results: In the overall cohort, SVI was not associated with outcomes on cardiac pathology in multivariable-adjusted models. However, in stratified multivariable-adjusted analyses, higher SVI (higher social vulnerability) was associated with a higher odds of myocardial fibrosis among individuals without clinical diagnoses of HF. Conclusions: Higher indices of social vulnerability are associated with a higher odds of myocardial fibrosis at autopsy among individuals without known clinical diagnoses of HF. Potential pathophysiological mechanisms and implications for prevention/treatment of myocardial dysfunction require further study.